Improving Understanding of Technopreneurship to Motivate the Community to Engage in Technology-Based Entrepreneurship in Hegarmanah Village, Bungbulang, Garut Regency - Rahayu, Dinar; Nugraha, Yopi; Rosliani, Elin; Suherlan, Encep Riswan (Fakultas Kewirausahaan Universitas Garut, 2024)
Over time, the growth of entrepreneurship has increasingly been supported by advancements in technology. This has encouraged many entrepreneurs to start utilizing technology in their businesses. The combination of entrepreneurship and technology has given rise to a new term in the business world: Technopreneurship. Hegarmanah Village is located in Bungbulang District, Garut Regency. This village leverages various potentials within its area, such as agriculture, plantations, forests, livestock, home industries, creative human resources, and more. The presence of residents involved in home industries indicates that the community in Hegarmanah Village is already engaged in entrepreneurship. However, they have yet to fully utilize technology for the sustainability of their businesses. Addressing this issue, the goal and solution of this study is to conduct a seminar on Technopreneurship to help the community better understand the importance of incorporating technology into their entrepreneurial activities. The methodology used in this study is descriptive, aiming to provide an overview of specific phenomena or aspects of life within the community currently being studied. Based on the observations during the implementation of the activities, there has been a noticeable improvement in the community's knowledge and skills related to technology-based entrepreneurship. This demonstrates that the entrepreneurial spirit can be nurtured and developed through a combination of activities that include Education, Entrepreneurship, Technology, and Entertainment, which can foster the spirit of technopreneurship. Additionally, the use of digital technology has proven capable of enhancing entrepreneurial abilities and skills.